Modeling and Testing of 3D Wound Core Loss of Amorphous Alloy Transformer for Photovoltaic Inverter - Peng Chen; Jianwei Han; Xinglong Yao; Xiaohui Wang; Yunfei Yan; Zhe Zhao; Lisong Zhang; Zhanyang Yu; Hao Li (Energies)
The harmonic content of transformers used in the field of new energy is significantly higher than that of conventional transformers, leading to an abnormal increase in transformer loss during operation. Therefore, the loss characteristics of amorphous alloy transformers are investigated in this paper. First, a measurement platform for the magnetic property of transformer cores under sinusoidal excitation is developed. The magnetization characteristics, loss characteristics and loss composition of the amorphous alloy core under sinusoidal excitation are measured and analyzed. On this basis, the traditional Steinmetz loss calculation formula is modified, and the loss calculation formula is further refined by improving its coefficients to accommodate various frequencies. Secondly, using a field-circuit coupling method, a 3D model of the transformer core is established by finite element simulation. The magnetic flux distribution and core losses are computed under both sinusoidal excitation and non-sinusoidal excitation. Finally, the impact of core rotation magnetization on the magnetic flux density is considered, and experimental errors are minimized by applying an empirical formula. The numerical model validity and accuracy are verified by comparing the simulation results with experimental data.